Edge Computing for the Infrastructure - Bahl, Victor (Future of Information and Communications Conference 2020, 2020)
Bahl explores the edge computing paradigm from the perspective of a researcher who has worked on this since its inception over a decade ago. He discusses the evolution of the intelligent edge, describes real-world applications and products; the progress made & lessons learned as they developed and deployed Rocket, an edge-cloud live video analytics system. Rocket is part of several pilots including Vision Zero, aimed at reducing traffic-related fatalities, and improving urban mobility. Bahl also takes a peek into the future and predicts how the telecommunication industry will embrace edge computing as part of it’s infrastructure. He lays out a few technical and business challenges facing large-scale adoption and the opportunities that are been created.